PELATIHAN PEMBUATAN MODUL AJAR BERBASIS APLIKASI KVISOFT FLIPBOOK MAKER BAGI PARA GURU PONDOK PESANTREN TARBIYAH ISLAMIYAH - Widiawati, Widiawati; Santoso, Yulianto; Alkadri, Hanif; Susanti, Lusi; Gistituati, Nurhizrah (Jurnal Abdi Masyarakat, 2023)
Digital developments require the learning process to shift from conventional face-to-face learning in class towards the use of information technology. The current use of information technology is able to shift the paradigm from the use of printed books to the use of digital format books with good quality content, a more attractive, interactive and cost-effective appearance/packaging. The importance of digital books to support the learning process is currently felt in all lines of education. One application that can be used to create attractive, interactive, and cost-effective digital books is Kvisoft Flipbook Maker. However, the phenomenon in the field shows that most teachers do not know and have not been able to create teaching modules using the Kvisoft Flipbook Maker application. Therefore, this community service activity aims to improve teachers' ability to create teaching modules using the Kvisoft Flipbook Maker application. The service was carried out at the Tarbiyah Islamiyah Pasia Islamic Boarding School. A total of 15 teachers were involved in this training. The results of the training show that the training conducted can improve the ability of teachers to make teaching modules using the kvisoft flipbook maker application. The training was carried out very well where the students were enthusiastic and focused on participating in the training. The average percentage of training effectiveness is 95.33%..